O ensino religioso no espaço público escolar: uma análise da tradição cristã na abordagem pós-colonial - Figueiredo, Adriana Guilherme Dias da Silva (2018)
This dissertation is linked to the Master's Degree in Religious Sciences of the Catholic University of Pernambuco, in the line of research: Brazilian religious field, culture and society. It aims to analyze Religious Education in the schools of the Municipal Network in Recife, in the light of the presuppositions of the postcolonial approach, seeking to understand its relation with the curricular decolonization and the displacements in the references of the Christian tradition, as well as the concretization of a secular teaching and in harmony with the religious diversity, both from the bibliographical survey about the theme, and from the concepts expressed by teachers located in three schools of the referred network. Considering the particularities surrounding the formation of the Brazilian state, whose fusion between religion and politics was the mark of the political-economic project of Portuguese territorial expansion, we initially sought to contextualize the aspects related to the constitution of secularism in Brazil and the establishment of Religious Education to then present the references of the postcolonial approach through bibliographic review. This is a field research with a qualitative and descriptive approach. Thus, the data collection was done through semi-structured interviews applied to the eleven interviewees having as complementary instrument the semiparticipant observation of the classes of Religious Education taught in the three schools that were the field of this research, with the purpose of analyzing what were the understandings and the concepts about secularity and religion and their relationship with the implementation of the principle of secularity and religious diversity, as well as to analyze the religious contents present in their practice in order to establish relations between them and the contents conveyed in the teaching proposal of the New policy of the educational network, regarding Religious Education and the treatment of the Christian tradition. The analysis of the collected data was carried out from the content analysis, where, after the identification of the general categories, we selected the final categories for the problematization of the discussed thematic axes. As a result, we hope to contribute to the expansion of the debates about lay religious teaching and attentive to the religious diversity present in the daily school life, through actions and practices capable of promoting the inclusion of the margins once subsumed and silenced by Eurocentrism, which includes tradition Christian, beyond the mere polarization between his hegemony or rejection, rather, constructing a dialogical perspective.